Osteoimmunology - Fonseca, João Eurico; Caetano-Lopes, Joana (Henry Stewart Talks, 2010)
Osteoimmunology, Bone structure, Crosstalk between osteoblasts and osteoclasts, Immunoregulation of bone, Direct influence of the immune system on bone, Osteoimmunoendocrinology, Effects of immune activation on bone structure
Archived at 2018/05/31